PENGEMBANGAN TUJUAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI INDONESIA - Fadli Padila Putra (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
The curriculum is one of the elements often cited as the cause of the decline in the quality of education. The curriculum has many complaints, including being too dense, not in accordance with the needs of students, too burdensome for students, and making it difficult for teachers. As a result, there will be some improvements in curriculum construction. The aims of this study were: 1) to analyze the curriculum from the perspective of Islamic religious education, 2) to analyze the theory of formulation of curriculum objectives, and 3) to analyze the theory of developing curriculum objectives. This study uses a type of library research. Documentation is used in the data collection process, and data sources from various related references are analyzed. The study's results explain curriculum objectives play an essential role in guiding all teaching activities and coloring other curriculum elements. Developing curriculum objectives is compiling, implementing, assessing, and perfecting these objectives to be even better. In developing curriculum objectives, five principles must be considered, namely the principles of relevance, flexibility, continuity, efficiency, and effectiveness.